Pengetahuan dan Sikap Tentang Rokok-Narkotika-Psikotropika-Zat Adiktif pada Masa Setelah Pandemic Covid-19, pada Siswa Usia 14-17 Tahun: Studi Deskriptif Korelatif: Knowledge and Attitudes About Cigarettes-Narcotics-Psychotropics-Addictive Substances in the Post-Covid-19 Pandemic Period, in Students Aged 14-17 Years: A Correlative Descriptive Study - Susilo, Eko; Wakhid, Abdul; Rosyidi, M. Imron (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2024)
Adolescent knowledge and attitudes about smoking are important aspects in the context of adolescent growth and development. The purpose of this study was to identify smoking behavior, knowledge and attitudes about smoking, narcotics, psychotropics, and other addictive substances in the post-COVID-19 pandemic period in students aged 14-17 years. A descriptive correlative study was chosen in this study with a sample of 333 respondents who were sampled using the consecutive sampling technique. Data collection was carried out using a knowledge questionnaire and an adolescent attitude questionnaire about smoking. Data analysis was carried out using descriptive analysis and bivariate analysis with chi square. it was found that the age of the respondents did not have a significant relationship with the knowledge and attitudes of respondents about smoking, narcotics, psychotropics, and addictive substances, respectively the p value was 0.754 and 0.381. The knowledge and attitude factors about smoking, narcotics, psychotropics, and addictive substances in high school students are important to monitor and evaluate with the continuation of efforts to improve the knowledge and attitudes of respondents towards the good category. ABSTRAK Pengetahuan dan sikap remaja tentang merokok merupakan aspek penting dalam konteks pertumbuhan dan perkembangan remaja. Tujuan dari penelitian ini adalah untuk mengidentifikasi perilaki merokok, pengetahuan dan sikap tentang merokok, narkotika, psokotropika, dan zat adiktif lainnya pada masa setelah pandemic covid-19 pada siswa usia 14-17 tahun. Studi descriptive korelatif dipilih dalam penelitian ini dengan sampel sejumlah 333 responden yang dilakukan pengambilan sampel dengan Teknik consecutive sampling. Pengumpulan data dilakukan dengan menggunakan kuesioner pengetahuan dan kuesioner sikap remaja tentang merokok. Analisis data dilakukan dengan menggunakan analisis descriptive dan analisis bivariat dengan chi square. didapatkan bahwa usia responden tidak memiliki hubungan yang signifikan dengan pengetahuan dan sikap responden tentang merokok, narkotika, psokotropika, dan zat adiktif, secara berurutan nilai p adalah 0,754 dan 0,381. Faktor pengetahuan dan sikap tentang merokok, narkotika, psokotropika, dan zat adiktif pada remaja siswa SMA penting untuk dilakukan monitoring dan evaluasi dengan keberlanjutan upaya peningkatan pengetahuan dan sikap responden menuju kategori baik.